Maskerade af Ludvig Holberg: iscenesat af Charlotte Munksø, Grønnegårds Teatret - Kuhlmann, Annelis (Peripeti, 2022)
Holberg’s Maskerade A review of Grønnegårds Teatrets’s production of Maskerade (dir. Charlotte Munksø), Copenhagen July and August 2022.